PRIMARY HYPERPARATHYROIDISM IN PREGNANCY, INITIAL PRESENTATION WITH HYPOCALCAEMIA SECONDARY TO ACUTE PANCREATITIS AND SEPSIS - Gnanasegaran, Alvin; Mugilarassan, Sivasangkari (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND Diagnosis of primary hyperparathyroidism is challenging during pregnancy and requires special care to prevent complications such as nephrolithiasis, pancreatitis, preterm delivery and foetal demise. We are reporting a rare case of primary hyperparathyroidism initially presenting with severe hypocalcaemia. CASE A 25-year-old primigravida at 24 weeks of gestation was admitted to intensive care unit with decompensated septic shock and acute kidney injury requiring ventilatory support. Subsequently, she had chorioamnionitis and nonviable foetus resulting in premature delivery. CECT of the abdomen showed acute pancreatitis in the absence of gallstone and caecal perforation with extensive peritonitis. She then underwent laparotomy. Other laboratory results showed elevated white blood count (29.7 g/d) and serum creatinine (173 micromol/L) with reduced eGFR (35 ml/mol/1.73 m2), hypocalcaemia (1.79 mmol/L (corrected)), hypoalbuminemia (21 g/L), with normal phosphate (0.91 mmol/L). She required multiple intravenous calcium corrections for the first 3 days. The serum calcium showed gradual increment from 2.4 mmol/l to 4.07 mmol/L within 10 days without calcium or vitamin D supplementation and adequate hydration. Intact parathyroid hormone (iPTH) was 43 pmol/L but repeat test was elevated at 148 pmol/L. She required intravenous zolendronate 4 mg with bridging calcitonin given 3 weeks apart. She had severe vitamin D deficiency of <5 ng/mL for which she was started on replacement. Patient denied familial hypercalcaemia or MEN syndrome. Ultrasound of the neck did not locate a parathyroid adenoma. Therefore, she is awaiting sestamibi scan and genetic testing to rule out familial causes of primary hyperparathyroidism is being considered. CONCLUSION Hypocalcaemia is a common finding in acute pancreatitis due to mesenteric calcium salt formation. It is also present in critically ill patients with sepsis which is a marker of severity with increased mortality and hospital stay. Hypercalcaemia was unmasked later in this case upon the resolution of the above-mentioned conditions. During pregnancy, surgery is the treatment of choice during the second trimester in cases of severe hypercalcemia (calcium>3.0 mmol/L) because medical therapy options are unsafe.